Associations between various obesity-related indicators and hypertension: a national cross-sectional survey with 117,609 Chinese adults - Chenglong Wang; Yini Wu; Mingjian Nie; Duobujie; Chenhui Xiao; Wanglong He; Chaoqun Fan; Qiang Feng; Jingjing Wang (Frontiers in Public Health, 2026)
Objective To evaluate how well obesity-related indicators (ORIs) discriminate hypertension in Chinese adults, thereby identifying the best-performing metrics and clarifying their dose–response associations with hypertension. Methods This study analyzed data from the 2020 National Physical Fitness Surveillance Database, comprising 117,609 adults aged 20–79 years with complete data on 10 ORIs and relevant covariates. Receiver Operating Characteristic (ROC) curves were employed to evaluate the discriminatory ability of ORIs for hypertension, with Youden’s Index (sensitivity + specificity −1) used to determine optimal cut-off values for identifying individuals at high risk. Based on the comparative evaluation, ORIs with the highest AUC values were selected for further analysis using multivariable logistic regression and restricted cubic spline (RCS) models to investigate their dose–response relationships with hypertension. Results The weighted prevalence of hypertension among Chinese adults was 24.79%. Among the 10 ORIs, body roundness index (BRI) and waist-to-height ratio (WHtR) exhibited the highest discriminatory ability for hypertension in the overall population and across sex-stratified subgroups (AUC: overall = 0.686, males = 0.647, females = 0.721). The optimal cut-off values for BRI and WHtR in the overall population were 3.66 and 0.52, respectively. Multivariable logistic regression models demonstrated that each unit increase in BRI z-score (OR = 1.51, 95% CI: 1.48–1.53) and WHtR z-score (OR = 1.53, 95% CI: 1.50–1.55) was associated with a 51% increased possibility of hypertension in the overall population. Individuals with BRI and WHtR values at or above the identified thresholds had a 2.00-fold and 1.97-fold increased possibility of hypertension, respectively, compared with those below the thresholds. RCS revealed a nonlinear dose–response relationship between BRI/WHtR and hypertension ( p for nonlinear <0.05). Sensitivity analyses substantiated the robustness of these discriminatory and associative findings. Conclusion Both BRI and WHtR, as abdominal obesity indices that simultaneously incorporate waist circumference and height, demonstrated highly consistent performance in discriminating hypertension among adults. BRI values below 3.66 and WHtR values below 0.52 potentially conferring a substantial reduction in hypertension possibility.